Pengaruh Pendapatan Asli Daerah (Pad), Dana AlokasiUmum (Dau), Dan Dana Alokasi Khusus (Dak) TerhadapPertumbuhan Ekonomi Di Kabupaten/Kota ProvinsiJawa Tengah Periode 2012-2013 - Wijanarko, Denny, Atwal Arifin, Drs., Akt.,M.Si (2015)
This study aims to determine the effect of PAD, DAU and DAK to economic growth in the district / city in Central Java province in the period 2012-2013. This research uses descriptive study, which used data types using secondary data from the financial statements of the district / city in the form of balance sheet, the realization of the budget, and the budget in the districts / cities in Central Java Province which consists of 29 counties and six cities in the period 2012- 2013. The study population is the district / city in Central Java province, and a sample of 35 districts / cities in Central Java province. Analysis of data using multiple regression analysis. The results of the analysis proved that by value t count variable revenue of 12.740, while the value of the t-table with a confidence level of 0.05 is 1.670 so the H1 accepted, meaning PAD significant effect on economic growth. Based on the t-value variable DAU count of 0,703, while the value of the t-table with a confidence level of 0.05 is 1,670 so that H2 is rejected, meaning DAU no significant effect on economic growth. Then, based on the value t count variable fund at 0.219, while the value of the t-table with a confidence level of 0.05 is 1,670 so H3 is rejected, meaning DAK no significant effect on economic growth.